Who Helps Single Mothers in Nairobi? The Role of Kin Support. Issue 4 (28th April 2017) - Clark, Shelley; Madhavan, Sangeetha; Cotton, Cassandra; Beguy, Donatien; Kabiru, Caroline
Abstract: Single mothers often turn to their extended kin for financial assistance and to help with child care. Such support may be especially important in areas of high poverty and poor environmental conditions. Using novel kinship data, this article assesses the extent of support given by more than 3, 000 relatives to 462 single mothers living in a slum area of Nairobi, Kenya. Contrary to stereotypes about families in sub‐Saharan Africa, the active kin network of single mothers is relatively small, and nearly a fifth of mothers do not receive any financial or child‐care assistance. Different types of kin offer different kinds of support according to culturally proscribed roles. However, support also depends heavily on kin's employment status, geographic proximity, and age. These findings offer a nuanced picture of how single women living in slum areas draw on their kin network to cope with their daily demands as mothers.